APLIKASI AKAD SYIRKAH DALAM LEMBAGA KEUANGAN SYARIAH - Saripudin, Udin (Jurnal Al-Amwal, 2018)
Syirkah or syarikah is a form of mixing in Islam whose operational pattern is inherent in the principle of business partnership and profit sharing. Syirkah is a concept that can precisely solve capital problems. Syirkah is very important in the economic growth of the community. The occurrence of economic stagnation often occurs because the owner of the capital is unable to manage his own capital or vice versa has the ability to manage capital but does not have the capital, it can be solved in syirkah which is justified in Islamic sharia. This paper attempts to uncover syirkah from a theoretical and practical perspective through several literature studies and observations of a number of Islamic financial institutions